My father, the shape shifter Ang tatay kong nagpapalit-palit ng hugis - Sevilla, Maria Cecilia (Lampara books, 2013)
"Luis father is away at sea to make their life as a family more comfortable. Because of this, Luis terribly misses his father. But Luis' father ahs an extraordinary quality that quenches his and his mother's loneliness as a result of their missing him. read in this story about the secret of Luis' father and how he manages to be with them despite the fact that he is far away."